Immune-Mediated Disorders Causing Bleeding or Thrombosis in Lymphoproliferative Diseases - Lechner, Klaus; Pabinger, Ingrid; Obermeier, Hanna Lena; Knoebl, Paul (Seminars in Thrombosis and Hemostasis, 2014)
Bleeding and thrombosis are important complications in patients with malignant lymphomas. They may be due to direct actions of the lymphoma, such as venous compression or bone marrow infiltration, but they may also be caused by paraneoplastic phenomena, which are immune-mediated in most of the cases. The most important paraneoplastic immune-mediated disorders in lymphomas causing bleeding are autoimmune thrombocytopenia, acquired hemophilia A and acquired von Willebrand syndrome. In addition, there are a variety of other less common immune-mediated bleeding conditions, such as acquired thrombasthenia, acquired factor X-, V-, XI-, XII-, or prothrombin deficiency. The presence of antiphospholipid antibodies is a rare condition predisposing to venous and arterial thrombosis and there are other very uncommon conditions, which predispose exclusively to arterial thrombosis such as hyperlipidemic xanthomatosis. Interestingly, there is hardly any correlation between the histological type and the aggressiveness of lymphoma and the type and prevalence of the immune-mediated conditions. Successful treatment of the underlying lymphoma is often associated with definite and sustained resolution of the immune-mediated disorder.
Keywords: lymphoma; autoimmune complications; thrombosis; bleeding; treatment